2018
DOI: 10.1111/mec.14934
|View full text |Cite
|
Sign up to set email alerts
|

Genomic and transcriptomic signals of thermal tolerance in heat‐tolerant corals (Platygyra daedalea) of the Arabian/Persian Gulf

Abstract: Scleractinian corals occur in tropical regions near their upper thermal limits and are severely threatened by rising ocean temperatures. However, several recent studies have shown coral populations can harbour genetic variation in thermal tolerance. Here, we have extended these approaches to study heat tolerance of corals in the Persian/Arabian Gulf, where heat‐tolerant local populations experience extreme summer temperatures (up to 36°C). To evaluate whether selection has depleted genetic variation in thermal… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
65
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 64 publications
(68 citation statements)
references
References 109 publications
(174 reference statements)
3
65
0
Order By: Relevance
“…This tolerance arises from many genes of small effect (multilocus adaptation) and suggests that the lack of fixed differences mean there are tradeoffs to thermal tolerance. Similarly, Kirk et al () found 131 loci in Platygyra daedalea that were correlated with larval thermal tolerance, but that effect sizes were small, supporting the multilocus model for heat tolerance. Rose, Bay, Morikawa, and Palumbi () also documented polymorphisms associated with thermal tolerance between cryptic species and found expression quantitative trait loci (eQTLs) in the study populations.…”
Section: Fixed Host Effects Contribute To Thermal Tolerancementioning
confidence: 85%
See 3 more Smart Citations
“…This tolerance arises from many genes of small effect (multilocus adaptation) and suggests that the lack of fixed differences mean there are tradeoffs to thermal tolerance. Similarly, Kirk et al () found 131 loci in Platygyra daedalea that were correlated with larval thermal tolerance, but that effect sizes were small, supporting the multilocus model for heat tolerance. Rose, Bay, Morikawa, and Palumbi () also documented polymorphisms associated with thermal tolerance between cryptic species and found expression quantitative trait loci (eQTLs) in the study populations.…”
Section: Fixed Host Effects Contribute To Thermal Tolerancementioning
confidence: 85%
“…The authors found that the transcriptomic responses to thermal stress of parents and offspring were broadly similar and demonstrated that maternal input was more important than paternal, but that having both parents from thermally tolerant populations further improved heat tolerance and accounted for 87% of deviance in larval survival under stress (Dixon et al, 2015). A similar result in heat stressed larvae of Platygyra daedalea showed that heat tolerance is highly heritable, with paternal genotype explaining ~70% of variation in thermal tolerance (Kirk, Howells, Abrego, Burt, & Meyer, 2018).…”
Section: Heritability Of Thermal Tolerancementioning
confidence: 94%
See 2 more Smart Citations
“…High‐throughput methods used to identify such biomarkers include whole genome/transcriptome sequencing and resequencing, genotyping by sequencing, restriction‐site associated DNA (RAD) sequencing, and amplicon sequencing (reviewed by Matz, ). One benefit of investing in the downstream development of genomic markers is that many studies aimed at uncovering the genomic basis of adaptive trait variation in corals have already identified putative markers for further development (e.g., Bay & Palumbi, , ; Dixon et al., ; Jin et al., ; Kirk, Howells, Abrego, Burt, & Meyer, ; Kitchen et al., ; Lundgren et al., ). Additionally, DNA sequences are more fixed than any other type of biomarker, and are therefore the most amenable to predictive assays.…”
Section: Molecular Biomarker Discoverymentioning
confidence: 99%